ANALISIS ISI KUANTITATIF PENERAPAN KOMUNIKASI KRISIS DALAM SEKOLAH SWASTA IMBAS PPPK - Kerfin; Anom, Erman (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
The purpose of this research is to analyze the application of crisis communication in private schools impacted by Government Employees with Contract Agreements or PPPK. This type of research is quantitative content analysis. Quantitative content analysis is a research method that focuses on research with keywords in news texts or reading texts which are the main focus of research. The data source for this research is primary data by taking news samples from 3 different online media, however, they are similar to each other both in terms of the title and the content of the news. The results of this study show that 1) the percentage of implementing crisis communication in the first news reaches 75% with three of the four questions. 2) the percentage of implementing crisis communication in the second story reaches 50% with two of the four questions. 3) the percentage of implementing crisis communication in the third news reaches 50% with two of the four questions.